Characterization of mucin gene expression and goblet cell proportion in inflammatory colorectal polyps in miniature dachshunds - TAKIGUCHI, Mitsuyoshi; OHTA, Hiroshi; YOKOYAMA, Nozomu; NAKAMURA, Kensuke; SASAKI, Noboru; NAGATA, Noriyuki; TEOH, Yong Bin (Journal of Veterinary Medical Science, 2022)
Hyperplastic goblet cells and abundant mucus are significant characteristics of inflammatory colorectal polyps (ICRPs) in miniature dachshunds. In this study, selected mucin gene expressions and goblet cell proportions were evaluated in miniature dachshunds with ICRPs and in healthy dogs. Mucin 2 (MUC2) gene expression was not significantly different among the groups, whereas mucin 5AC (MUC5AC) gene expression was significantly higher in the polypoid lesions than in healthy colonic mucosa. Although the percentage of goblet cells in the upper crypt regions did not significantly differ between the groups, that in the lower crypt regions was significantly decreased in polypoid lesions. In conclusion, increased MUC5AC gene expression and goblet cell proportion changes may be associated with the pathogenesis of ICRPs.